1996
DOI: 10.1042/bj3130617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic AMP and prostaglandin E2 on the induction of nitric oxide- and prostanoid-forming pathways in cultured rat mesangial cells

Abstract: Cyclic AMP (cAMP) represents an important cellular signalling molecule. We analysed the effect of dibutyryl cAMP (db-cAMP), a cell-permeable and stable derivative of cAMP, on the regulation and expression of cyclo-oxygenase 2, inducible NO synthase and argininosuccinate synthetase. We observed different transcriptional regulation of these enzymes depending on the dbcAMP concentration used. Low concentrations of db-cAMP in the range 10-50 µM elevated levels of cyclo-oxygenase 2 mRNA, protein and activity, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
2
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 34 publications
(34 reference statements)
2
16
2
1
Order By: Relevance
“…Similar effects have also been seen in renal mesangial cells (13,18) and brown adipocytes (19). Although cAMP alone does not induce iNOS in unstimulated cardiac myocytes, it augments iNOS induction in interleukin-1␤-stimulated cells (20).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Similar effects have also been seen in renal mesangial cells (13,18) and brown adipocytes (19). Although cAMP alone does not induce iNOS in unstimulated cardiac myocytes, it augments iNOS induction in interleukin-1␤-stimulated cells (20).…”
Section: Discussionsupporting
confidence: 51%
“…An increase in intracellular cAMP levels is an important intracellular signaling mechanism involved in the regulation of gene expression. Certain in vitro studies have shown that an increase in cAMP levels causes iNOS induction (12)(13)(14), whereas in other studies, increased cAMP levels caused a reduction in iNOS (15,16). In the present study, we explored the intracellular signaling pathway for the LPS-induced increase in cAMP levels and its involvement in LPSstimulated NO production in RAW 264.7 macrophages.…”
mentioning
confidence: 97%
“…Different studies reported that the increase of intracellular cAMP level enhanced PGHS-2 expression in various cell types (17)(18)(19)(20). In agreement with these findings, we established that forskolin, which enhances intracellular cAMP level by stimulating adenylyl cyclase, significantly increases PGHS-2 expres- sion in HPMECs.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, the increase of intracellular cAMP rate enhances PGHS-2 expression in various cell types (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In HaCaT cells, treatment with forskolin induces a transient phosphorylation of both CREB and ATF-1, and a 2 ± 3-fold induction of COX-2 promoter activity that is dependent on the COX-2 CRE. Interestingly, elevation of cellular level of cAMP also up-regulates the expression of endogenous COX-2 (Nusing et al, 1996;Oshima et al, 1991). Thus, a correlation exists between the phosphorylation of CREB or ATF-1 and the COX-2 promoter activity.…”
Section: Discussionmentioning
confidence: 99%